Characteristics of gene mutations in Vietnamese medullary thyroid carcinoma patients: a single-center analysis - Van Hung Pham; Quoc Thang Pham; Minh Nguyen; Hoa Nhat Ngo; Thao Thi Thu Luu; Nha Dao Thi Minh; Trâm Đặng; Anh Tu Thai; Hoang Anh Vu; Dat Quoc Ngo (Journal of Pathology and Translational Medicine)
Background The RET gene point mutation is the main molecular alteration involved in medullary thyroid carcinoma (MTC) tumorigenesis. Previous studies in Vietnam mainly consisted of case reports, with limited data on larger sample sizes. In this study, we investigated RET gene mutations in exons 10, 11, and 16 and analyzed clinicopathological features of a series of Vietnamese MTC patients. Methods We collected 33 tissue samples from patients with MTC and analyzed RET mutations using the Sanger sequencing method. The relationship between hotspot RET mutations (exons 10, 11, 16) and clinicopathological features were investigated. Results Among the 33 analyzed cases, 17 tumors (52%) harbored RET mutations in exon 10, 11, or 16. A total of 10 distinct genetic alterations were identified, including eight missense mutations and two short indels. Of these, seven were classified as pathogenic mutations based on previous publications, with p.M918T being the most frequent (4 cases), followed by p.C634R (3 cases) and p.C618R (3 cases). Mutations were significantly associated with specific histological patterns, such as the nested/insular pattern (p=.026), giant cells (p=.007), nuclear pleomorphism (p=.018), stippled chromatin (p=.044), and amyloid deposits (p=.024). No mutations were found in germline analyses, suggesting these were somatic alterations. Conclusions Our results provided the first comprehensive analysis of RET mutations in Vietnamese MTC patients. The most frequent mutation was p.M918T, followed by p.C634R and p.C618R. Mutations in these three exons were linked to specific histopathological features. Information on mutational profiles of patients with MTC will further aid in the development of targeted therapeutics to ensure effective disease management.